2001
DOI: 10.1159/000050095
|View full text |Cite
|
Sign up to set email alerts
|

Improved Survival in Small Pancreatic Cancer

Abstract: Background: Although the incidence of pancreatic cancer is relatively low compared with other tumors (2.4%), the death rate is high. Tumor detection and treatment at an early stage is necessary to improve the poor prognosis of patients, as is demonstrated by some reports showing a 5-year survival rate varying between 19 and 41% for patients undergoing radical pancreatectomy with the highest survival in patients with small tumors. Methods: In our study we retrospectively reviewed the histologic and demographic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 58 publications
0
12
0
Order By: Relevance
“…The survival of patients with pancreatic cancer could be good if the tumor were to be detected at an early stage ,. Of note, the advantage of surgical resection over chemoradiotherapy has not been confirmed yet, and we have two choices for the treatment of pancreatic cancer.…”
Section: Introductionmentioning
confidence: 99%
“…The survival of patients with pancreatic cancer could be good if the tumor were to be detected at an early stage ,. Of note, the advantage of surgical resection over chemoradiotherapy has not been confirmed yet, and we have two choices for the treatment of pancreatic cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Although the concept of the PanIN (Pancreatic intraepithelial neoplasia) classification (8) has been proposed, many papers still describe pancreatic cancers as small or early. In addition, it has been suggested that radical resection with extensive soft tissue clearance might be more important for prognosis than tumor size alone (9, 10). Degrees of epithelial atypia of the cystic dilated lesions, corresponding to PanIN classifications, may be important in the detection of early-stage pancreatic cancers (11, 12).…”
Section: Discussionmentioning
confidence: 99%
“…In the many reviews of surgical treatment of pancreatic carcinoma, the overall 5‐year survival rate was around 10% 2,3 , 10,11 . To our knowledge, there are few reports of s‐PC 7,11–18 . To determine whether small, probably early cancers represent the curable condition, we reviewed the clinicopathological features and postoperative results of patients who underwent curative surgery for s‐PC.…”
Section: Discussionmentioning
confidence: 99%